Equipment Efficiency Analysis of Espresso Machine Using the Overall Equipment Effectiveness (OEE) Method and Total Productive Maintenance (TPM) Approach - Ni Matul Azizah; Rizky Dermawan; Ratih Mukti Azhar (Jurnal Akuntansi, Manajemen dan Ekonomi, 2026)
This study aims to evaluate the equipment efficiency of a La Marzocco espresso machine at Kopi Anak Monopole Coffee Shop by employing the Overall Equipment Effectiveness (OEE) method and the Total Productive Maintenance (TPM) framework. The analysis measures machine performance through three main OEE components: availability, performance, and quality. A quantitative approach was used by collecting eight months of observational data (December 2024–July 2025), including operational time, downtime, setup duration, and the quantity of both good and defective outputs. Data interpretation involved OEE computation, the Six Big Losses framework, Pareto prioritization, and Fishbone root-cause analysis. Findings indicate that before TPM implementation, the espresso machine achieved an average OEE of 30.25%, dominated by idling and minor stoppages (65.61%). After TPM was applied, the OEE increased to 31.01%, showing measurable improvement in machine reliability and operator awareness. The study highlights that the adoption of TPM principles in small-scale coffee shops can enhance operational discipline and efficiency, offering both theoretical and practical insights for service oriented businesses.